Strategies to recognize, use and master the plural form of nouns in the learning-teaching process, in third year of bachelorship. - Balseca Espinoza, Luis Fernando (Machala : Universidad Técnica de Machala, 2015)
The theoretical dimension of the practical case is to be solved by the investigation of strategies to teach vocabulary in which students dominate and recognize plural noun forms easily.
La dimensión teórica del caso práctico ha de ser resuelto por la investigación de estrategias para enseñar vocabulario en el que dominan los estudiantes y reconocer las formas plurales de sustantivos fácilmente.
Keywords: MASTER; NOUN; TEACHING-LEARNING; STRATEGY